Pengaruh Pengurangan Setting Time (Wait on Cement) pada Semen Tahan Api dengan Penambahan Oil Well Cement - Bayu Rahmadika; Yayuk Apriyanti; Irvani Irvani (MINERAL, 2017)
Underground Coal Gasification (UCG) is a technology to extract coal deposits in the form of gas from mineral deposit without disassembling of overburden. There are some initial processes in UCG, one of them is cementing to glue the casing into the formation. This research-based laboratory using cement mixture that consists of Fire Mortar as the main ingredients with added Oil Well Cement (OWC) by 40%, 42.5%, 45%, 47.5%, 50%, 52.5%, 55%, 57.5% and 60% of the total weight of the cement mixture. Cement samples were then tested with hydration heat test, furnace test at temperatures of 300°C to 900°C and UCS test of a sample at normal temperature as well as samples that have undergone combustion at a certain temperature. Composition of OWC>50% have faster setting time on the 29th to 40th hours with maximum hydration temperature of 34.4°C on the 11th to the 12th hour as well as getting the optimal composition of Fire Mortar which is 42.5% and OWC which is 57.5%. Composition of 50-60% Fire Mortar have a heat resistance to a maximum of 900°C so they don’t experience failure and cracks which make a sample split. Ofter than that, composition of 50-60% OWC on average have a greater compressive strength with the highest compressive strength value of 1.75 MPa at a temperature of 500°C.